ANALISIS RASIO KEUANGAN SEBAGAI ALAT UNTUK MENGEVALUASI KINERJA KEUANGAN PADA PT. KALBE FARMA Tbk DI BURSA EFEK INDONESIA - Maharani H., Friska; Amiranto, Jianto B. (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTThe financial report is a very important tool to obtain information relating to the financial position and the results achieved by the company. So that the financial statements may mean for the parties concerned it is necessary to conduct the analysis of the relationship of financial statement items. Ratio analysis can be used to give a picture of the actual financial situation of the company and whether the company is doing a healthy business. Problems taken is how the company's financial performance at PT. Kalbe Farma Tbk in 2011-2014. This research uses descriptive method that uses quantitative data in the form of financial keuangan.Laporan reports obtained from the Indonesia Stock Exchange in Surabaya located at Jl. Manyar Pumpungan 30 Surabaya.Sedangkan an analytical tool used in this research is to use analysis ratios include the ratio of liquidity, solvency, activity and profitability. Results of the study analyzes the current ratio shows that PT. Kalbe Farma Tbk. able to pay off current debt with its current assets. Because every Rp.1 of current liabilities secured Rp 3.33 in current assets. Analysis of the quick ratio is able to meet its obligations due to any debt secured Rp 1 current liabilities secured Rp 2.18 in current assets. Research activity ratio, the ratio used no 4. First, the average age of the company's receivables exceeding the due payment agreement. While the average age of receivables generated approximately 2 months of payments. Inventory, supply turnaround occurs every 120 days in a year. Inventory turnover going pretty well. Fixed asset turnover calculation results PT. Kalbe Farm Tbk. capable of producing penjulan amounted to 4.40. Total asset turnover is high enough to generate sales for the year 2011-2014 in the amount of 1.40 of its assets. The solvency ratio, debt to equity ratio is increasing every year it can be concluded that the company is able to meet its obligations to the capital owned. Debt to asset ratio shows the ability of the asset whose value is higher than the value of the debt. Means the asset is able to meet the obligations of the company. Profitability ratios, results of calculation of the profit margin PT. Kalbe Farma Tbk in 2011 the value of the calculation of the resulting 14.1%, but in the year 2012 to 2014 has decreased. Results of calculation return on assets shows the assets owned by the company is able to generate a profit of 18% from 2011-2014. The calculation result shows the company's return on equity is high enough to generate profits from the capital of the company by 23% from 2011-2014. Keywords: Financial Statements, Financial Ratios, and Financial Performance